Old and New Matrix Algebra Useful for Statistics - Minka, Tom (1997)
A concise reference on advanced matrix theory, including: • an easy way to compute matrix derivatives and second derivatives • a general framework for inverting partitioned matrices • useful properties of Kronecker product, Hadamard product, and diag • the column-stacking operator "vec" and its generalization to "vec-transpose" with applications to multilinear models, principal component analysis, blind source separation, Lyapunov equations, model alignment, and more.